Glaucoma : a patient's guide to the disease - Trope, Graham E. (University of Toronto Press, 2011)
"Essential information about glaucoma and its treatment is presented here in a simple question-and-answer format to allow patients to participate actively in the decision-making process along the road to successful maintenance of their vision."--Page i